Routledge handbook of esports - Jenny, Seth E. (Routledge, Taylor & Francis Group, 2025)
This handbook offers the first fully comprehensive, interdisciplinary study of esports, one of the fastest growing sectors of the contemporary sports and entertainment industries. Global in coverage, it emphasizes the multifaceted nature of esports and explores the most pressing issues defining the competitive video gaming landscape today.
Keywords: E-Sport